Effect of foliar spraying with boron, potassium and seaweed extract on production indicators of apple (Journal of Hama University, 2025)
This research was conducted in Lattakia Governorate on apple tree variety (Golden delicious) in order to find out the effect of foliar spraying with boron, potassium and marine algae extract on the percentage of nodes and the fall of June and the fruiting coefficient of apple trees Golden delicious, the research included spraying with potassium, boron and marine algae individually or in combination with each other. Spraying with these substances led to the superiority of the studied treatments compared to the control, the increase in the percentage of nodes was observed significantly when spraying with a mixture of potassium, boron and marine algae extract (T8) (44.84)% for the average of the two years compared to the control (T1) (34.07)%, and the treatment of marine algae (T4) gave the lowest percentage of fruit precipitation in the month of June for the average of the two years (24.59)% and the highest percentage of increase was in the treatment of the witness (T1) (61.89)%, as well as an increase was found in the percentage of fruiting coefficient, where all treatments outperformed the control and the highest value was in the treatment of boron, potassium and marine algae extract together, where it reached in the average of the two years (T8) (22.13) %, while the control treatment (T1) was (12.18)%.